Analysis of the role of international network effects on the diffusion of second and third generation mobile communication networks - Maria Baquero; Toshifumi Kuroda (International Telecommunications Society (ITS), 2015)
Using quarterly data of 58 countries, this paper provides empirical evidence that mobile phone diffusion from 2007 to 2009 is positively influenced by international network effects. Direct and indirect network effects are a result of the international standadization of telecommunication technologies, which allows consumers in a given country to benefit from other countries' networks by using international roaming services or imported handsets. We define international network effects as the installed base of mobile phone subscribers in countries different than the home country which use the same technology, weighted by various distance metrics. (geographic distance, trade value of mobile handsets and number of personal travelers between the home country and the partner countries.) To measure international network effects, we estimate a series of differentiated-products demand-system models of mobile phones by technology standard with international network effects. To overcome the endogeneity of mobile service price and international network effects, we propose two new instrumental variables (IV). In addition, we test if the impact on mobile phone diffusion differs whether technologies are local or global standards, or whether they are backward/formard-combatible. Based on our findings, we conclude that the large network effects of GSM (Global System for Mobile Communications) technology prevent the diffusion of third generation (3G) mobile phones. We show that the high 3G diffusion rates in Japan and Korea are not driven by state-of-the-art technology or high consumer preference, but by the absence of the GSM standard. Finally, to assess teh effect of technology choice on welfare in Japan, we conduct a counterfactual analysis an demonstrate thar if the GSM technology was introduced in Japan, it would increase Japanese monthly per-consumer surplus from 94.2 to 188.
Keywords: L15; L96; F10; 330; Cellular telephony; Diffusion; Global standards; Network effect